Gambaran Pasien Infeksi Saluran Kemih Di Ruang Rawat Inap Sebuah Rumah Sakit Swasta Di Purwokerto - Anang Kurniawan; Ary Nahdiyani Amalia; Indrawati Aris Tyarini (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Purpose: This study was to determine the description of urinary tract infection patients in the inpatient ward of a private hospital in Banyumas. Methodology: This study used an analytic observation method with a cross-sectional approach, to see the description of patients with urinary tract infections. Results: Of the 40 samples studied for 3 months, the sample characteristics were based on gender, the highest number of urinary tract infection sufferers was female with a total of 22 people (55%) and the lowest was in males (45%). Based on sample characteristics according to age, the highest number of UTI sufferers occurred at the age of more than 60 years (50%) and the lowest was at the age of 30 to 40 years (17.5%). Conclusion: The conclusion of this study is that urinary tract infections have a risk along with increasing age and female sex.